The resort city of Kołobrzeg: how it is extending its borders, rebuilding its transport system and expanding its economic profile - Miedziński, Mariusz (Turystyka w badaniach podstawowych, 2023)
The COVID-19 pandemic has had a very significant impact on the functioning of cities and areas with strongly developed and dominant tourist and spa functions. During the pandemic, the largest Polish health resort and one of the largest tourist centers in the country took advantage of the opportunities offered by the seaport as well as the functioning of a very strong local development sector. The crisis experience of the COVID-19 pandemic motivated residents, entrepreneurs and authorities to take decisive action to change the current economic and functional profile of the city. The years 2019–2022 were therefore spent on developing and implementing changed administrative borders, rebuilding and improving internal and external transport accessibility, as well as starting efforts to develop the seaport and new non-tourist functions of the city. After the pandemic, Kołobrzeg has a chance to become a significant, multifunctional, medium-sized city with a strong and diversified economy and still a leading tourist and health resort. The extension of the city limits, the introduction of new functions, the reconstruction of the railway and the port with further improvement of transport accessibility are the most groundbreaking activities aimed at maintaining and further increasing the importance of Kołobrzeg as the largest and most important tourist center next to Gdańsk on the Polish coast.